[tex]a)\\\\\sqrt{16*9}=\sqrt{16}*\sqrt{9}=4*3=12\\\\b)\\\\\sqrt{100*64}=\sqrt{100}*\sqrt{64}=10*8=80\\\\c) \\\\\sqrt{6^2*5^2}=\sqrt{6^2}*\sqrt{5^2}=6*5=30\\\\d)\\\\\sqrt{4*81*9}=\sqrt{4}*\sqrt{81}*\sqrt{9}= 2*9*3=54[/tex]
[tex]e)\\\\\sqrt{16*25*49}=\sqrt{16}*\sqrt{25}*\sqrt{49}=4*5*7=140\\\\f)\\\\\sqrt{11^2*2^2*3^4}=\sqrt{11^2}*\sqrt{2^2}*\sqrt{(3^2)^2}=11*2*3^2=22*9=198\\\\g)\\\\\sqrt[3]{27*64}=\sqrt[3]{27 }*\sqrt[3]{64}=\sqrt[3]{3^3 }*\sqrt[3]{4^3}=3*4=12\\\\h)\\\\\sqrt[3]{8*64}=\sqrt[3]{8 }*\sqrt[3]{64}=\sqrt[3]{2^3 }*\sqrt[3]{4^3}=2*4=8[/tex]
[tex]i)\\\\\sqrt[3]{7^3*3^3}= \sqrt[3]{7^3 }*\sqrt[3]{3^3}= 7*3=21\\\\j)\\\\\sqrt[3]{27*64*125}= \sqrt[3]{27}*\sqrt[3]{64}*\sqrt[3]{125}=\sqrt[3]{3^3 }*\sqrt[3]{4^3}*\sqrt[3]{5^3}= 3*4*5=60\\\\k)\\\\\sqrt[3]{3^6*5^3*2^9}= \sqrt[3]{(3^2)^3 }*\sqrt[3]{5^3}*\sqrt[3]{(2^3)^3}= 3^2*5*2^3=9*5*8=360\\\\l)\\\\\sqrt[3]{4^9*6^3*27}=\sqrt[3]{(4^3)^3 }*\sqrt[3]{6^3}*\sqrt[3]{3^3}=4^3*6*3=64*18=1152[/tex]